(untitled) (Aporte Santiaguino, 2019)
A proposal is presented in which the respective energy analysis is carried out to characterize the calorific value of commercial gasolines in Ecuador as: Super, Extra and Ecopaís. This study is carried out in the laboratory of internal combustion engines of the University of the Armed Forces-ESPE, with the purpose of obtaining mathematical models that relate the energy and quality parameters of gasolines.Models that will be obtained through computational tools such as artificial neural network (ANN), which will use a set of historical data provided by the Agency for Regulation and Control of Hydrocarbons (ARCH) of Ecuador, for validation.